Hereditary Angioedema and Gastrointestinal Complications: An Extensive Review of the Literature - Napoleon Patel; Lisbet D. Suarez; Sakshi Kapur; Leonard Bielory (Case Reports in Immunology)
Hereditary Angioedema (HAE) is a rare autosomal dominant (AD) disease characterized by deficient (type 1) or nonfunctional (type 2) C1 inhibitor protein. The disorder is associated with episodes of angioedema of the face, larynx, lips, abdomen, or extremities. The angioedema is caused by the activation of the kallikrein-kinin system that leads to the release of vasoactive peptides, followed by edema, which in severe cases can be life threatening. The disease is usually not diagnosed until late adolescence and patients tend to have frequent episodes that can be severely impairing and have a high incidence of morbidity. Gastrointestinal involvement represents up to 80% of clinical presentations that are commonly confused with other gastrointestinal disorders such as appendicitis, cholecystitis, pancreatitis, and ischemic bower. We present a case of an HAE attack presenting as colonic intussusception managed conservatively with a C1 esterase inhibitor. Very few cases have been reported in the literature of HAE presentation in this manner, and there are no reports of any nonsurgical management of these cases.